Synthesis and characterization of oil palm empty fruit bunch- grafted -polyvinyl alcohol (OPEFB-g-PVA) hydrogel for removal of copper ions from aqueous solution - Wen, S.J. (American Institute of Physics Inc., 2017)
Oil palm empty fruit bunch (OPEFB) fiber is a natural polymer which is potentially used as efficient adsorbents for heavy metal cations. The main objective of this research is to synthesize OPEFB grafted polyvinyl alcohol (PVA) hydrogel by using ammonium persulfate (APS) as initiator and gelatin as crosslinking agent. The grafting temperature, amounts of cross linking agent, initiator and concentration of OPEFB were manipulated in order to optimize the swelling capability of the hydrogel. Comparison of heavy metal adsorption performance between pure PVA hydrogel and optimized OPEFB-g-PVA hydrogel was evaluated by using copper ions solution. The characteristics and structure of the optimized OPEFB-g-PVA hydrogel was studied by using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM) while Thermogravimetric Analysis (TGA) was used to study its thermal stability. The presence of band at 1088 and 1047cm-1 corresponds to C-O was observed as strong evidence of grafting. Water uptake capacity was evaluated and the maximum water absorption capacity was obtained at 180.67 g/g. PVA hydrogel with OPEFB proved to have better copper ion absorbency and thermal properties compared to pure PVA hydrogel. © 2017 Author(s).